Ionic liquid and preparation method thereof, surface-modified silicon dioxide and application thereof
By using imidazole salt-based ionic liquids to modify the surface of silica, the problem of limited number of surface graft functional groups is solved, the compatibility of silica and organic resin is significantly improved, and the performance of composite materials is improved.
Patent Information
- Application Number
- CN202110644607.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-06-09
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2041-06-09
AI Technical Summary
The number of surface grafting functional groups of existing surface modified silica is limited and the graft density is not high, resulting in poor surface modification effect of silica, affecting the compatibility between silica and organic resin.
The surface modification of silica is carried out using imidazole salt ionic liquid, grafting onto the surface of silica by hydrolysis of silicon oxide, and enriching the surface functional group type of silica by unsaturated functional groups, thereby increasing the graft density of the single silicon hydroxyl site functional groups.
The compatibility between silica and organic resin is significantly improved, the filling rate and dispersion of silica in organic resin is enhanced, and the thermal expansion performance and mechanical properties of composite materials are improved.
Smart Images

Figure CN115448943B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of functional materials, and in particular relates to an ionic liquid and a preparation method thereof, as well as a surface-modified silica and an application thereof. Background Art
[0002] Silica spherical powder is widely used as a filler to fill polymer and organic resin matrices to reduce the thermal expansion coefficient of composite materials due to its low thermal expansion coefficient and high heat and moisture resistance. The thermal expansion coefficient of composite materials is related to the filling amount of silica filler. The higher the filling amount of silica, the lower the thermal expansion coefficient of the composite material. However, as the filling amount of silica increases, silica tends to agglomerate and cannot be evenly dispersed in the organic resin, causing a series of problems.
[0003] A large number of studies and practices have shown that the surface modification of silicon dioxide using silane coupling agents can greatly improve the dispersibility of silicon dioxide. An important reason why silane coupling agents improve the dispersibility of silicon dioxide is that the silane coupling agent bonds to the hydroxyl sites on the surface of carbon dioxide, and couples a layer of functional groups similar to the functional groups of organic resins on the surface of silicon dioxide. Based on the principle of like dissolves like, silicon dioxide can be well dispersed in the organic resin matrix. For example, in some research works, researchers have used KH-560 silane coupling agent to modify silicon dioxide to improve the compatibility of silicon dioxide with organic resin matrix materials. The silica filler obtained by this method has a single modified component, good repeatability, easy verification and analysis of the modification results, and low cost. In addition, some researchers have tried to modify silicon dioxide with a variety of monofunctional silane coupling agents, such as using KH-550 aminosilane coupling agent and epoxy silane coupling agent to modify the surface of silicon dioxide nanoparticles at the same time. Compared with the modification of silica by KH-560 silane coupling agent alone, this method of modifying silica can simultaneously graft two or more monofunctional silane coupling agents onto the surface of silica, increasing the types of grafted functional groups. Moreover, after adding the silica nanoparticles obtained by this method to the phenolic organic resin, the heat resistance and mechanical properties of the organic resin can be improved. Nevertheless, when the above method is used to modify silica nanoparticles, due to the limited number of hydroxyl groups at the surface modification sites of silica, the number of functional groups on the surface after coupling and grafting is small, and the number of functional groups grafted on the surface is still limited. The miscibility of the modified silica with the organic resin matrix is insufficient, which limits the dispersibility of silica in the organic resin; at the same time, due to the steric effect on the surface of the silica nanoparticles, the grafting density of the epoxy group is not high, and the overall modification effect is not ideal. Summary of the invention
[0004] The purpose of the present application is to provide an ionic liquid and a preparation method thereof, as well as a surface-modified silica and its application, aiming to solve the problem that the number of grafted functional groups on the surface of the existing surface-modified silica is limited, the grafting density is not high, resulting in poor surface modification effect of silica and affecting the compatibility between silica and organic resin.
[0005] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0006] The first aspect of the present application provides an imidazolium salt ionic liquid, the general structural formula of which is shown in Formula 1 below:
[0007]
[0008] In formula 1, X - is an ionic liquid anion, R1 and R2 are independently selected from a group having 1 to 6 carbon atoms, R3 is selected from a group containing an unsaturated functional group, R 41 , R 42 , R 43 Each is independently selected from an alkyl group having 1 to 4 carbon atoms.
[0009] The imidazolium salt ionic liquid provided in the present application has two nitrogen-containing sites, one of which is connected to a siloxane group, so that the imidazolium salt ionic liquid can be grafted onto the surface of silica through hydrolysis of the siloxane group, thereby realizing surface modification of silica; the other nitrogen-containing site is connected to a group containing an unsaturated functional group, thereby enriching the types of grafted functional groups on the surface of silica through the unsaturated functional groups in the imidazolium salt ionic liquid, and increasing the grafting density of the single silanol site functional group on the surface of silica, thereby improving the compatibility between silica and the organic resin.
[0010] In a possible implementation, the group having 1 to 6 carbon atoms includes -CH2-, -C2H4-, -C3H6-, -C4H8-, -C5H 10 -、-C6H 12 -, -C2H2-, -C3H4-, -C4H6-, -C5H8-, -C6H 10 -, -CO-, -C2H2O-, -C3H4O-, -C4H6O-, -C5H8-O, -C6H 10 O-. These groups have a suitable carbon chain length, which is conducive to the hydrolysis and grafting of siloxane groups, and can reduce the steric hindrance of multi-branched siloxane groups to R3, increase the contact probability of unsaturated functional groups with organic resins, and thus improve the compatibility between silica modified with imidazolium salt ionic liquids and organic resins. Among them, when the imidazolium salt ionic liquid contains -C2H2-, -C3H4-, -C4H6-, -C5H8-, -C6H10 -, -CO-, -C2H2O-, -C3H4O-, -C4H6O-, -C5H8-O, -C6H 10 When the imidazolium salt ionic liquid is modified with silica, it can also increase the grafting density of the single silanol site functional group on the surface of silica and enrich the types of functional groups, thereby increasing the compatibility between silica and organic resins to a certain extent. Of course, due to the large steric hindrance of the unsaturated functional groups in R1 and R2, the improvement effect on the compatibility between silica and organic resins is not as significant as that of R3.
[0011] In a possible implementation, the R1 and R2 are each independently selected from -CH2-, -C2H4-, -C3H6-, -C4H8-, -C5H 10 -or-C6H 12 -. When R1 and R2 are the above groups, the imidazolium salt ionic liquid formed is easy to prepare and has less steric hindrance, which is conducive to the grafting of the imidazolium salt ionic liquid with silica, and further promotes the contact between the unsaturated group and the organic resin, thereby improving the compatibility between the silica modified by the imidazolium salt ionic liquid and the organic resin.
[0012] In a possible implementation, the unsaturated functional group includes at least one of -CH=CH-, -C(O)-, carboxylate, phenyl, and polysulfide. After the imidazole salt ionic liquid is grafted on the surface of silica, the unsaturated functional group in R3 can improve the compatibility between silica and organic resins. In particular, when R3 contains multiple unsaturated functional groups, the grafting density of the single silanol site functional group on the surface of silica is significantly increased, and the effect of improving the compatibility between silica and organic resins is more obvious.
[0013] In a possible implementation, R3 is selected from -COCH2CH=CH2, -CH=CHCH2CH2COCH=CH2, -C(COCH3)=CHCH=CHCH3, -CH=CHCH2CH2COOCH=CH2 or -C6H5-COCH2CH=CH2. R3 is an imidazolate ionic liquid of the above groups, which has a significant effect of improving the compatibility between silica and organic resin.
[0014] In a possible implementation, the R 41 , the R 42 , the R 43 Each is independently selected from methyl or ethyl. 41 , R 42 , R 43When each is independently selected from a methyl group or an ethyl group, the siloxane group in the imidazolium salt ionic liquid is easily hydrolyzed and broken, thereby enabling the imidazolium salt ionic liquid to be grafted onto the surface of silicon dioxide.
[0015] In a possible implementation, the X - One selected from bis(pentafluoroethylsulfonyl)imino anion and halogen anion. The above anions can form stable ionic liquids with the imidazolate cations in the above embodiments. Among them, the halogen anion forms hydrochloric acid under certain conditions, which has a certain corrosiveness to the grafted silicon dioxide. Therefore, the grafting conditions and the preservation of the grafted silicon dioxide material have higher requirements. The large-volume anion bis(pentafluoroethylsulfonyl)imino ion not only has good stability, but also does not cause corrosion to the grafted silicon dioxide material.
[0016] In a possible implementation, the imidazolium salt ionic liquid comprises the following structure:
[0017]
[0018]
[0019]
[0020] The above-mentioned imidazolium salt ionic liquid, after being grafted onto the surface of silicon dioxide, can effectively improve the compatibility between silicon dioxide and organic resin.
[0021] The second aspect of the present application provides a method for preparing an imidazolium salt ionic liquid, comprising the following steps:
[0022] Provide an imidazolium-type ionic liquid (R 41 O)(R 42 O)(R 43 O) SiR1C3H3N2 and an organic compound A-R2-R3, wherein A is a halogen, R1 and R2 are each independently selected from a group having 1 to 6 carbon atoms, R3 is selected from a group containing an unsaturated functional group, and R 41 , R 42 , R 43 Each is independently selected from an alkyl group having 1 to 4 carbon atoms;
[0023] In an inert atmosphere or under vacuum conditions, the imidazolium ionic liquid (R 41 O)(R 42 O)(R 43 O) SiR1C3H3N2 is mixed with an organic substance A-R2-R3, and heated to react to obtain the imidazole salt ionic liquid described in the first aspect of the present application; or the imidazole ionic liquid (R41 O)(R 42 O)(R 43 O) SiR1C3H3N2 is mixed with the organic matter A-R2-R3, heated for reaction, and after the reaction is completed, an anion salt is added to the reaction system to replace the halogen in the synthesized ionic liquid to obtain the imidazole salt ionic liquid described in the first aspect of the present application.
[0024]
[0025] The preparation method of the imidazole salt ionic liquid provided in the present application only requires the imidazole type ionic liquid (R 41 O)(R 42 O)(R 43 O) SiR1C3H3N2 and organic matter A-R2-R3 are heated to react to obtain the imidazole salt ionic liquid described in the first aspect of the present application. The method is simple to operate, the process is easy to control, and the production cost of the imidazole salt ionic liquid can be controlled.
[0026] In a possible implementation, the imidazolium ionic liquid (R 41 O)(R 42 O)(R 43 In the step of mixing SiR1C3H3N2 with the organic matter A-R2-R3, the imidazole type ionic liquid (R 41 O)(R 42 O)(R 43 O)SiR1C3H3N2 and the molar ratio of the organic matter A-R2-R3 is 1 to 1.5:1. In this case, the imidazole ionic liquid (R 41 O)(R 42 O)(R 43 O)SiR1C3H3N2 can react effectively with organic matter A-R2-R3 in a suitable molar ratio, especially when the imidazolium ionic liquid (R 41 O)(R 42 O)(R 43 When the amount of SiR1C3H3N2 is excessive, the excess imidazole ionic liquid (R 41 O)(R 42 O)(R 43 O)SiR1C3H3N2 can promote the reaction of the two in the direction of superpositive reaction and improve the reaction efficiency. It should be noted that imidazole ionic liquid (R 41 O)(R 42 O)(R 43 When the content of O)SiR1C3H3N2 is too high, it is easy to cause residues in the prepared imidazolium salt ionic liquid, affecting the purity and performance of the imidazolium salt ionic liquid.
[0027] In a possible implementation, the heating reaction temperature is 50-80°C and the reaction time is 24-72 hours. 41 O)(R 42 O)(R 43 O)SiR1C3H3N2 reacts with the organic matter A-R2-R3 to generate the ionic liquid shown in Formula 1, and the occurrence of side reactions can be reduced, thereby improving the yield and purity of the obtained ionic liquid.
[0028] The third aspect of the present application provides a surface-modified silica, including silica particles, and a modifier bound to the surface of the silica particles, wherein the modifier includes the product of removing the alkyl group in the alkoxysilyl group from the imidazolium salt ionic liquid as described in the first aspect of the present application.
[0029] The surface-modified silica provided by the present application has the product of removing the alkyl group in the alkoxysilyl group from the imidazolium salt ionic liquid described in the first aspect of the present application bonded to the surface of the silica particles. The silica particles into which the imidazolium salt ionic liquid is introduced have a richer type of functional groups at the single silanol site, and the grafting density is increased. These functional groups promote the contact between the silica and the organic resin, thereby improving the compatibility of the two.
[0030] In a possible implementation, the weight of the modifier is 0.2-5% of the weight of the silica particles. In this case, the modifier is grafted onto the surface of the silica particles at a suitable density to improve the surface properties of the silica, thereby improving the compatibility between the silica and the organic resin.
[0031] In a possible implementation, the particle size of the silicon dioxide particles is 300 nm to 5 μm. In this case, the silicon dioxide particles have a suitable specific surface area and number of surface hydroxyl groups, which are conducive to the grafting of macromolecular imidazole salt ionic liquid modifiers.
[0032] In a possible implementation, the modified compound is the product of removing the alkyl group in the alkoxysilyl group from the imidazolium salt ionic liquid. In this case, there is only one modification on the surface of the silica particles, which is the product of the hydrolysis of the imidazolium salt ionic liquid shown in Formula 1. The imidazolium salt ionic liquid increases the type of the hanging energy group and the grafting density of the silica, thereby improving the compatibility with the organic resin.
[0033] The fourth aspect of the present application provides a method for preparing surface-modified silicon dioxide, comprising the following steps:
[0034] The silicon dioxide powder is mixed with the imidazolium salt ionic liquid described in the first aspect of the present application, and reacted at a temperature of 80 to 200° C. to obtain the surface-modified silicon dioxide described in the second aspect of the present application.
[0035] The present application provides a method for preparing surface-modified silica, which comprises reacting silica powder and an imidazolium salt ionic liquid as shown in Formula 1 at a suitable temperature to obtain silica with a surface modified with an imidazolium salt ionic liquid. The method is simple and easy to control. More importantly, the silica with a surface modified with an imidazolium salt ionic liquid obtained in the method has an increased type and number of surface unsaturated functional groups, which can improve its compatibility with organic resins.
[0036] In a possible implementation, the reaction time is 0.5-3 hours. At a reaction temperature of 80-200° C., the silicon dioxide powder and the imidazolate ionic liquid described in the first aspect of the present application react for 0.5-3 hours, which is conducive to a full reaction between the two.
[0037] The fifth aspect of the present application provides a composite material, comprising an organic resin and a filler, wherein the filler is the surface-modified silica described in the third aspect of the present application.
[0038] The composite material provided in the present application includes an organic resin and a surface-modified silica filler. Since the surface of the silica is modified with an imidazolium salt ionic liquid, the compatibility between the organic resin and the silica filler can be enhanced, and the filling rate and dispersibility of the silica in the organic resin can be improved, so that the silica can fully play the role of reducing the thermal expansion performance of the composite material.
[0039] In a possible implementation, the weight ratio of the organic resin to the filler is 7:3 to 4:6, based on 10 parts by weight of the composite material. When the contents of the organic resin and the filler are within this range, the compatibility between the organic resin and the silica filler is enhanced, which is beneficial to improving the filling rate and dispersibility of silica in the organic resin, thereby giving the composite material better reliability.
[0040] In a possible implementation, the organic resin is selected from at least one of bisphenol F epoxy resin and bisphenol A epoxy resin. Such organic resin is compounded with surface-modified silica filler, and the two increase the compatibility with each other through the imidazolate ionic liquid (the product of the hydrolysis of the imidazolate ionic liquid shown in Formula 1) on the surface of silica, thereby improving the uniformity and performance stability of the composite material, and helping silica to fully play the role of reducing the thermal expansion performance of the composite material.
[0041] The sixth aspect of the present application provides an electronic component, including a printed circuit board, a filling glue layer located on at least one surface of the printed circuit board, and a chip arranged on the side of the filling glue layer away from the printed circuit board, wherein the filling glue in the filling glue layer is the composite material provided in the fifth aspect of the present application.
[0042] The electronic components provided in the present application include a filling glue comprising an organic resin and a surface-modified silica filler. Since the surface of the silica is modified with an imidazolium salt ionic liquid, a plurality of identical or different functional groups are simultaneously grafted onto a single silanol site of the silica, thereby achieving an effect of doubling the compatibility of the silica filler and the organic resin, thereby improving the effective filling rate and dispersion uniformity of the silica in the organic resin, enhancing the fluidity of the filling glue, reducing the thermal expansion coefficient, and ultimately improving the reliability of the chip.
[0043] In a possible implementation, the weight ratio of the organic resin to the filler is 5:5 to 4:6, based on 10 parts by weight of the composite material. When the contents of the two are within this range, the silicon dioxide is evenly dispersed in the composite material formed by the silicon dioxide and the organic resin, thereby giving the filling glue layer better thermal stability and improving the reliability of electronic components.
[0044] In a possible implementation, the organic resin is selected from at least one of bisphenol F epoxy resin and bisphenol A epoxy resin. These organic resins and surface-modified silica fillers are used as a filling glue layer between a printed circuit board and a chip in an electronic component. Since the surface-modified silica has good compatibility with the organic resin, the silica filler can be effectively filled and evenly dispersed in the organic resin, thereby enhancing the fluidity of the filling glue, reducing the thermal expansion coefficient, and ultimately effectively improving the reliability of the chip.
[0045] A seventh aspect of the present application provides a chip protection shell, wherein the chip protection shell is made of the composite material provided in the fifth aspect of the present application.
[0046] The chip protection shell provided in the present application comprises raw materials including an organic resin and a surface-modified silica filler. Since the surface of the silica is modified with an imidazole salt ionic liquid, a plurality of identical or different functional groups are simultaneously grafted onto a single silanol site of the silica, thereby achieving an effect of doubling the compatibility of the silica filler and the organic resin, thereby improving the effective filling rate and dispersion uniformity of the silica in the organic resin, enhancing the fluidity of the chip protection shell material, reducing the thermal expansion coefficient, and ultimately achieving excellent reliability.
[0047] In a possible implementation, the weight ratio of the organic resin to the filler is 2:8 to 1:9, based on 10 parts by weight of the composite material. When the contents of the two are within this range, the silicon dioxide is evenly dispersed in the composite material formed by the silicon dioxide and the organic resin, thereby giving the chip protection shell material better thermal stability and improving the reliability of the chip protection shell.
[0048] In a possible implementation, the organic resin is selected from at least one of bisphenol F epoxy resin, bisphenol A epoxy resin, dicyclopentadiene epoxy resin, biphenyl epoxy resin, and o-cresol linear epoxy resin. These organic resins are mixed with surface-modified silica fillers and used as chip protection shell materials. Since the surface-modified silica has good compatibility with the organic resin, the silica filler can be effectively filled and evenly dispersed in the organic resin, thereby enhancing the fluidity of the chip protection shell material, reducing the thermal expansion coefficient, and finally obtaining excellent reliability.
[0049] The eighth aspect of the present application provides a conductor, comprising a conductor core, and a stacked insulating adhesive coated on the surface of the conductor core or formed on the surface of the conductor core joint, wherein the stacked insulating adhesive is made of the composite material provided in the fifth aspect of the present application.
[0050] The wire provided in the present application, the stacked insulating adhesive material includes an organic resin and a surface-modified silica filler. Since the surface of the silica is modified with an imidazole salt ionic liquid, a plurality of identical or different functional groups are simultaneously grafted on a single silanol site of the silica, thereby achieving the effect of exponentially improving the compatibility of the silica filler and the organic resin, thereby improving the effective filling rate and dispersion uniformity of the silica in the organic resin, enhancing the fluidity of the stacked insulating adhesive, reducing the thermal expansion coefficient, and ultimately obtaining excellent insulation and heat insulation properties.
[0051] In a possible implementation, the weight ratio of the organic resin to the filler is 6:4 to 4.5:5.5, based on 10 parts by weight of the composite material. When the contents of the two are within this range, the silicon dioxide is evenly dispersed in the composite material formed by the silicon dioxide and the organic resin, thereby reducing the thermal expansion coefficient of the stacked insulating adhesive, and ultimately obtaining excellent thermal insulation and insulating properties.
[0052] In a possible implementation, the organic resin is selected from at least one of bisphenol A epoxy resin, naphthalene epoxy resin, and dicyclopentadiene epoxy resin. These organic resins are mixed with surface-modified silica fillers to form a stacked insulating adhesive film for chips. Since the surface-modified silica has good compatibility with the organic resin, the silica filler can be effectively filled and evenly dispersed in the organic resin, thereby enhancing the fluidity of the stacked insulating adhesive, reducing the thermal expansion coefficient, and ultimately obtaining excellent insulation and heat insulation properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 It is a schematic diagram of the structure of the electronic components provided in the embodiment of the present application. DETAILED DESCRIPTION
[0054] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0055] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0056] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0057] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0058] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0059] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0060] The term “CTE” is an abbreviation for “Coefficient of thermal expansion”, and means coefficient of thermal expansion.
[0061] The composite material formed by filling unmodified or insufficiently modified silica as a filler in an organic resin has problems such as easy agglomeration of silica and difficulty in dispersion, resulting in low silica filling rate, poor fluidity, large thermal expansion coefficient, etc., which affects the process operation performance and reliability of the composite material.
[0062] When a silane coupling agent is used to modify silica, the overall modification effect is not obvious due to the steric hindrance effect of the silica surface and the limited number of surface silanol groups, which affects the compatibility of silica with organic resins. In view of this, the present application embodiment uses an ionic liquid that can introduce multiple unsaturated functional groups to modify silica, so that silica can be grafted with multiple and / or multiple functional groups at a single silanol site at the same time, thereby achieving the purpose of doubling the compatibility of silica fillers and organic resins.
[0063] In a first aspect, the present invention provides an imidazolate ionic liquid, the general structure of which is shown in Formula 1:
[0064]
[0065] In the embodiment of the present application, the general structure shown in Formula 1 contains an imidazole structure, and the imidazole structure contains two nitrogen sites, and the distance between the two nitrogen sites is one carbon atom. The imidazole salt ionic liquid cation provided in the embodiment of the present application introduces three alkoxysilyl chains at one nitrogen site, and the three alkoxysilyl groups are bonded to the hydroxyl groups on the surface of the silica particles after hydrolysis, and the imidazole salt ionic liquid is grafted on the surface of the silica to achieve surface modification of the silica. The other nitrogen site of the imidazole salt ionic liquid cation introduces a group containing an unsaturated functional group, which can enrich the types of unsaturated functional groups in the silica surface modifier and increase the grafting density of unsaturated functional groups at a single hydroxyl site on the silica surface. Due to the presence of a certain distance between the two nitrogen sites in the imidazole salt ionic liquid cation, the steric hindrance effect of the siloxane chain on the unsaturated functional group can also be reduced. After the imidazole salt ionic liquid of the structure shown in Formula 1 is combined on the silica surface, the surface properties of silica can be improved and the compatibility between silica and organic resin can be improved.
[0066] In the structure of Formula 1 in the embodiment of the present application, X - is the anion of the ionic liquid, X - The parts other than these constitute the cations of the imidazolium salt ionic liquid.
[0067] In the cation of the imidazolium salt ionic liquid, R1 forms a bridge between the siloxane group and the imidazole structure, and is mainly used to introduce an alkoxysilyl group at a nitrogen site of the imidazole structure in the process of preparing the imidazolium salt ionic liquid of the structure of formula 1. In the embodiment of the present application, R1 is selected from a group with a carbon number of 1 to 6. The appropriate carbon chain length of R1 can not only effectively hydrolyze the siloxane group in the imidazolium salt ionic liquid of the structure of formula 1, but also reduce the steric hindrance effect of the alkoxysilyl group on R2, R3, especially on R3 to a certain extent, which is beneficial to the imidazolium salt ionic liquid of the structure of formula 1, especially the surface modification of silicon dioxide by R3 in the structure of the imidazolium salt ionic liquid. If the number of carbon atoms in R1 is too much, the difficulty of hydrolysis of the siloxane group increases, and due to the corresponding increase in the carbon chain length of R1, the resulting steric hindrance effect increases instead, which will hinder the reaction between the alkoxysilyl group and the hydroxyl group on the surface of silicon dioxide, and affect the surface modification of silicon dioxide by the imidazolium salt ionic liquid of the structure shown in formula 1.
[0068] In one possible implementation, R1 is selected from -CH2-, -C2H4-, -C3H6-, -C4H8-, -C5H 10 -、-C6H 12 -, -C2H2-, -C3H4-, -C4H6-, -C5H8-, -C6H 10 -, -CO-, -C2H2O-, -C3H4O-, -C4H6O-, -C5H8-O, -C6H 10O-. These groups have a suitable carbon chain length, which is conducive to the hydrolysis and grafting of siloxane groups, and can reduce the steric hindrance of multi-branched siloxane groups to R3, increase the contact probability of unsaturated functional groups with organic resins, and thus improve the compatibility between silica modified with imidazolium salt ionic liquids and organic resins. Among them, when R1 of the imidazolium salt ionic liquid contains -C2H2-, -C3H4-, -C4H6-, -C5H8-, -C6H 10 -, -CO-, -C2H2O-, -C3H4O-, -C4H6O-, -C5H8-O, -C6H 10 When the imidazolium salt ionic liquid is modified with silica, it can also increase the grafting density of the single silanol site functional group on the surface of silica and enrich the types of functional groups, thereby increasing the compatibility between silica and organic resins to a certain extent. Of course, due to the large steric hindrance of the unsaturated functional group in R1, the contact probability between R1 and the organic resin is low after the imidazolium salt ionic liquid is modified with silica, so the improvement effect on the compatibility between silica and organic resins is not as significant as the improvement effect of R3 on the compatibility between silica and organic resins.
[0069] In some embodiments, R1 is selected from -C3H6-, -C4H8-, -C5H 10 -or-C6H 12 -. When R1 is the above-mentioned group, the siloxane group in the imidazolium salt ionic liquid can be effectively hydrolyzed, and the distance between the siloxane group and R3 can be increased, thereby reducing the steric hindrance effect of the siloxane group on R3. Exemplarily, -C3H6- includes (alkoxysilyl)-CH2CH2CH2-(imidazolyl), (alkoxysilyl)-CH(CH3)CH2-(imidazolyl), (alkoxysilyl)-CH2CH(CH3)-(imidazolyl). In one possible embodiment, -C3H6- selects (alkoxysilyl)-CH2CH2CH2-(imidazolyl) with smaller steric hindrance. Exemplarily, -C4H8- includes (alkoxysilyl)-CH2CH2CH2CH2-(imidazolyl), (alkoxysilyl)-CH(CH3)CH2CH2-(imidazolyl), (alkoxysilyl)-CH2CH(CH3)CH2-(imidazolyl), (alkoxysilyl)-CH2CH2CH(CH3)-(imidazolyl), (alkoxysilyl)-CH(C2H5)CH2-(imidazolyl), (alkoxysilyl)-CH2CH(C2H5)-(imidazolyl), (alkoxysilyl)-CH(C3H7)-(imidazolyl). In one possible embodiment, -C4H8- selects (alkoxysilyl)-CH2CH2CH2CH2-(imidazolyl) with less steric hindrance. Exemplarily, -C5H 10- including (alkoxysilyl)-CH2CH2CH2CH2CH2-(imidazolyl), (alkoxysilyl)-CH(CH3)CH2CH2CH2-(imidazolyl), (alkoxysilyl)-CH2CH(CH3)CH2CH2-(imidazolyl), (alkoxysilyl)-CH2CH2CH(CH3)CH2-(imidazolyl), (alkoxysilyl)-CH2CH2CH(CH3)CH2-(imidazolyl), (alkoxysilyl)-CH2CH2CH2CH(CH3)-(imidazolyl), (alkoxysilyl)-CH( C2H5)CH2CH2-(imidazolyl), (alkoxysilyl)-CH2CH(C2H5)CH2-(imidazolyl), (alkoxysilyl)-CH2CH2CH(C2H5)-(imidazolyl), (alkoxysilyl)-CH2CH(C3H7)-(imidazolyl), (alkoxysilyl)-CH(C3H7)CH2-(imidazolyl), (alkoxysilyl)-CH(C4H9)-(imidazolyl), in one possible embodiment, -C5H 10 -Select the (alkoxysilyl) -CH2CH2CH2CH2CH2-(imidazolyl) with less steric hindrance. Exemplary, -C6H 12 - including (alkoxysilyl)-CH2CH2CH2CH2CH2CH2-(imidazolyl), (alkoxysilyl)-CH(CH3)CH2CH2CH2CH2-(imidazolyl), (alkoxysilyl)-CH2CH(CH3)CH2CH2CH2-(imidazolyl), (alkoxysilyl)-CH2CH2CH(CH3)CH2CH2-(imidazolyl), (alkoxysilyl)-CH2CH2CH(CH3)CH2CH2-(imidazolyl), (alkoxysilyl)-CH2CH2CH2CH(CH3)CH2-(imidazolyl), (alkoxysilyl)-CH2CH2CH2CH(CH3)CH2-(imidazolyl), (alkoxysilyl)-CH2CH2CH2CH2CH(CH3)-(imidazolyl), (alkoxysilyl)-CH(C2H5)CH2CH2CH2-(imidazolyl), (alkoxysilyl) (alkoxysilyl)-CH2CH(C2H5)CH2CH2-(imidazolyl), (alkoxysilyl)-CH2CH2CH(C2H5)CH2-(imidazolyl), (alkoxysilyl)-CH2CH2CH2CH(C2H5)-(imidazolyl), (alkoxysilyl)-CH2CH(C3H7)CH2-(imidazolyl), (alkoxysilyl)-CH(C3H7)CH2CH2-(imidazolyl), (alkoxysilyl)-CH2CH2CH(C3H7)-(imidazolyl), (alkoxysilyl)-CH(C4H9)CH2-(imidazolyl), (alkoxysilyl)-CH2CH(C4H9)-(imidazolyl), (alkoxysilyl)-CH(C5H 11 )-(imidazolyl), in one possible embodiment, -C6H 12 -Select the (alkoxysilyl)-CH2CH2CH2CH2CH2CH2CH2-(imidazolyl) with less steric hindrance.
[0070] In the cation of imidazolium ionic liquids, R 41 , R 42 , R 43 is the alkyl group in the alkoxysilyl group in the imidazolium salt ionic liquid structure of Formula 1, and R in the embodiment of the present application 41 , R 42 , R 43 are each independently selected from an alkyl group having 1 to 4 carbon atoms. 41 , R 42 , R 43 The formed alkoxysilyl group can be effectively hydrolyzed. If the carbon chain length is too long, the difficulty of hydrolysis increases, thereby reducing the surface modification of silicon dioxide by the imidazolium salt ionic liquid of Formula 1. 41 , R 42 , R 43 Each is independently selected from methyl or ethyl. 41 , R 42 , R 43 When each is independently selected from methyl or ethyl, the siloxane group in the imidazolium salt ionic liquid is easily hydrolyzed and cleaved, thereby enabling the imidazolium salt ionic liquid to be grafted onto the surface of silicon dioxide. 41 , R 42 , R 43 Not required to be exactly the same, for example, R 41 , R 42 is methyl, R 43 is ethyl; or R 41 , R 42 Ethyl, R 43 is methyl; or R 41 , R 43 Ethyl, R 42 is methyl; or R 41 , R 43 is methyl, R 42 Of course, R 41 , R 42 , R 43 At the same time, it is methyl or ethyl.
[0071] In the cation of the imidazolate ionic liquid, R2 is a bridge between R3 and the imidazole structure, which is used to extend the carbon chain length and reduce the steric hindrance effect of the imidazole group on the unsaturated functional group in R3. In particular, when the carbon to which R3 and R2 are connected is an unsaturated carbon, the steric hindrance effect of the imidazole group on the unsaturated functional group can be effectively alleviated. In the embodiment of the present application, R2 is selected from a group having a carbon number of 1 to 6. The appropriate carbon chain length of R2 can increase the steric hindrance effect of the alkoxysilyl group on R3, which is beneficial to the surface modification of silicon dioxide by R3 in the imidazolate ionic liquid structure of formula 1, especially the imidazolate ionic liquid structure. If the number of carbon atoms in R2 is too large, the carbon chain length increases accordingly, and the resulting steric hindrance effect increases instead, which will not only increase the difficulty of grafting the imidazolate ionic liquid to silicon dioxide, but also increase the difficulty of contact between R3 and the organic resin, affecting the compatibility between silicon dioxide and the organic resin.
[0072] In one possible implementation, R2 is selected from -CH2-, -C2H4-, -C3H6-, -C4H8-, -C5H 10 -、-C6H 12 -, -C2H2-, -C3H4-, -C4H6-, -C5H8-, -C6H 10 -, -CO-, -C2H2O-, -C3H4O-, -C4H6O-, -C5H8-O, -C6H 10 O-. These groups have a suitable carbon chain length, which can reduce the steric hindrance of the multi-branched siloxane group to R3, increase the contact probability of the unsaturated functional group with the organic resin, and thus improve the compatibility between the silica modified with the imidazolium salt ionic liquid and the organic resin. Among them, when the R2 of the imidazolium salt ionic liquid contains -C2H2-, -C3H4-, -C4H6-, -C5H8-, -C6H 10 -, -CO-, -C2H2O-, -C3H4O-, -C4H6O-, -C5H8-O, -C6H 10 When the imidazolium salt ionic liquid is modified with silica, it can also increase the grafting density of the single silanol site functional group on the surface of silica and enrich the types of functional groups, thereby increasing the compatibility between silica and organic resins to a certain extent. Of course, compared with R3, since the unsaturated functional group in R2 is subject to greater steric hindrance, the contact probability between R2 and the organic resin is lower after the imidazolium salt ionic liquid is modified with silica, so the improvement effect on the compatibility between silica and organic resins is not as significant as that of R3.
[0073] In some embodiments, R2 is selected from -CH2-, -C2H4-, -C3H6-, -C4H8-, -C5H 10 -or-C6H12 -. When R2 is the above group, the distance between the siloxane group and R3 can be increased, and the steric hindrance effect of the siloxane group on R3 can be reduced. Exemplarily, -C2H4- includes (R3)-CH2CH2-(imidazolyl) and (R3)-CH(CH3)-(imidazolyl). Exemplarily, -C3H6- includes (R3)-CH2CH2CH2-(imidazolyl), (R3)-CH(CH3)CH2-(imidazolyl) and (R3)-CH2CH(CH3)-(imidazolyl). In one possible embodiment, -C3H6- selects (R3)-CH2CH2CH2-(imidazolyl) with smaller steric hindrance. Exemplarily, -C4H8- includes (R3)-CH2CH2CH2CH2-(imidazolyl), (R3)-CH(CH3)CH2CH2-(imidazolyl), (R3)-CH2CH(CH3)CH2-(imidazolyl), (R3)-CH2CH2CH(CH3)-(imidazolyl), (R3)-CH(C2H5)CH2-(imidazolyl), (R3)-CH2CH(C2H5)-(imidazolyl), (R3)-CH(C3H7)-(imidazolyl). In one possible embodiment, -C4H8- selects (R3)-CH2CH2CH2CH2-(imidazolyl) which has less steric hindrance. Exemplarily, -C5H 10 - includes (R3)-CH2CH2CH2CH2CH2-(imidazolyl), (R3)-CH(CH3)CH2CH2-(imidazolyl), (R3)-CH2CH(CH3)CH2CH2-(imidazolyl), (R3)-CH2CH2CH(CH3)CH2-(imidazolyl), (R3)-CH2CH2CH2CH(CH3)CH2-(imidazolyl), (R3)-CH(C2H5)CH2CH2-(imidazolyl), (R3)-CH2CH(C2H5)CH2-(imidazolyl), (R3)-CH2CH2CH(C2H5)-(imidazolyl), (R3)-CH2CH(C3H7)-(imidazolyl), (R3)-CH(C3H7)CH2-(imidazolyl), (R3)-CH(C4H9)-(imidazolyl), in one possible embodiment, -C5H 10 -Select (R3) -CH2CH2CH2CH2CH2-(imidazolyl) with less steric hindrance. Exemplary, -C6H 12- including (R3) -CH2CH2CH2CH2CH2CH2-(imidazolyl), (R3) -CH(CH3)CH2CH2CH2CH2-(imidazolyl), (R3) -CH2CH(CH3)CH2CH2CH2-(imidazolyl), (R3) -CH2CH2CH(CH3)CH2CH2-(imidazolyl), (R3) -CH2CH2CH(CH3)CH2CH2-(imidazolyl), (R3) -CH2CH2CH2CH(CH3)CH2-(imidazolyl), (R3) -CH2CH2CH2CH(CH3)CH2-(imidazolyl), (R3) -CH(C2H5)CH2CH2CH2-(imidazolyl), (R 3)-CH2CH(C2H5)CH2CH2-(imidazolyl), (R3)-CH2CH2CH(C2H5)CH2-(imidazolyl), (R3)-CH2CH2CH2CH(C2H5)-(imidazolyl), (R3)-CH2CH(C3H7)CH2-(imidazolyl), (R3)-CH(C3H7)CH2CH2-(imidazolyl), (R3)-CH2CH2CH(C3H7)-(imidazolyl), (R3)-CH(C4H9)CH2-(imidazolyl), (R3)-CH2CH(C4H9)-(imidazolyl), (R3)-CH(C5H 11 )-(imidazolyl), in one possible embodiment, -C6H 12 -Select (R3)-CH2CH2CH2CH2CH2CH2CH2-(imidazolyl) which has less steric hindrance.
[0074] In the cation of the imidazolium salt ionic liquid, R3 is selected from a group containing an unsaturated functional group. After the imidazolium salt ionic liquid provided in the embodiment of the present application is grafted onto the surface of silicon dioxide, the unsaturated functional group introduced by R3 modifies the surface of silicon dioxide, thereby improving the compatibility problem between silicon dioxide and organic resin.
[0075] In a possible implementation, the unsaturated functional group includes at least one of -CH=CH-, -C(O)-, carboxylate, phenyl, and polysulfide. In this case, after the imidazole salt ionic liquid is grafted on the surface of silica, the unsaturated functional group in R3 can improve the compatibility between silica and organic resins, especially when R3 contains multiple unsaturated functional groups, the grafting density of the single silanol site functional group on the surface of silica is significantly increased, and the effect of improving the compatibility between silica and organic resins is more obvious.
[0076] In one possible implementation, R3 is selected from a group containing two or more unsaturated functional groups. Thus, when the surface of silica is modified using the imidazolium salt ionic liquid shown in Formula 1, the grafting density of the unsaturated functional groups of the single hydroxyl group on the surface of silica can be increased, thereby better improving the compatibility between silica and the organic resin.
[0077] In some embodiments, R3 is selected from -COCH2CH=CH2, -CH=CHCH2CH2COCH=CH2, -C(COCH3)=CHCH=CHCH3, -CH=CHCH2CH2COOCH=CH2 or -C6H5-COCH2CH=CH. Ionic liquids of imidazolate salts in which R3 is the above groups have a significant effect of improving the compatibility between silica and organic resins.
[0078] In the formula 1 provided in the embodiment of the present application, X - is an ionic liquid anion. In one possible implementation, X - One selected from bis(pentafluoroethylsulfonyl)imino anion and halogen anion. The above anions can form stable ionic liquids with the imidazolate cations in the above embodiments. Among them, the halogen anion forms hydrochloric acid under certain conditions, which has a certain corrosiveness to the grafted silicon dioxide. Therefore, the grafting conditions and the preservation of the grafted silicon dioxide material have higher requirements. The large-volume anion bis(pentafluoroethylsulfonyl)imino ion not only has good stability, but also does not cause corrosion to the grafted silicon dioxide material.
[0079] In a possible implementation, the imidazolium salt ionic liquid comprises the following structure:
[0080]
[0081]
[0082]
[0083] The above-mentioned imidazolium salt ionic liquid, after being grafted onto the surface of silicon dioxide, can effectively improve the compatibility between silicon dioxide and organic resin.
[0084] The imidazolium salt ionic liquid provided in the first aspect of the embodiment of the present application can be prepared by the following method.
[0085] In a second aspect, the present invention provides a method for preparing an imidazolium salt ionic liquid, comprising the following steps:
[0086] S01. Provide an imidazole ionic liquid (R 41 O)(R 42O)(R 43 O) SiR1C3H3N2 and an organic compound A-R2-R3, wherein A is a halogen, R1 and R2 are each independently selected from a group having 1 to 6 carbon atoms, R3 is selected from a group containing an unsaturated functional group, and R 41 , R 42 , R 43 Each independently selected from an alkyl group having 1 to 4 carbon atoms
[0087]
[0088] In this step, the imidazolium ionic liquid (R 41 O)(R 42 O)(R 43 O)SiR1C3H3N2 and organic matter A-R2-R3 are used as raw materials to directly prepare imidazole salt ionic liquids of formula 1. 41 O)(R 42 O)(R 43 O) R1, R 41 , R 42 , R 43 The selection of R2 and R3 in the organic compound A-R2-R3 is as described above, and will not be repeated here to save space. 41 O)(R 42 O)(R 43 O)SiR1C3H3N2 and organic compound A-R2-R3 can be prepared by oneself or purchased from the market.
[0089] S02. In an inert atmosphere or vacuum condition, an imidazolium ionic liquid (R 41 O)(R 42 O)(R 43 O) SiR1C3H3N2 is mixed with an organic substance A-R2-R3, and heated to react to obtain the imidazole salt ionic liquid of the first aspect of the embodiment of the present application; or under an inert atmosphere or vacuum condition, the imidazole type ionic liquid (R 41 O)(R 42 O)(R 43 O) SiR1C3H3N2 is mixed with the organic matter A-R2-R3, heated for reaction, and after the reaction is completed, an anion salt is added to the reaction system to replace the halogen in the synthesized ionic liquid to obtain the imidazole salt ionic liquid of the first aspect of the embodiment of the present application.
[0090] This step is carried out under an inert atmosphere or vacuum conditions to prevent substances introduced into the gas environment from reacting with the raw materials or participating in the heating reaction, thereby affecting the preparation or purity of the product. Exemplarily, the inert atmosphere can be a nitrogen atmosphere, an inert gas atmosphere, a carbon dioxide atmosphere, or a nitrogen dioxide atmosphere.
[0091] In some possible embodiments, the imidazolium ionic liquid (R 41 O)(R 42 O)(R 43 When O)SiR1C3H3N2 is mixed with organic matter A-R2-R3, the imidazole type ionic liquid (R 41 O)(R 42 O)(R 43 O)SiR1C3H3N2 and the organic matter A-R2-R3 have a molar ratio of 1 to 1.5:1. In this case, the imidazole ionic liquid (R 41 O)(R 42 O)(R 43 O)SiR1C3H3N2 can react effectively with organic matter A-R2-R3 in a suitable molar ratio, especially when the imidazolium ionic liquid (R 41 O)(R 42 O)(R 43 When the amount of SiR1C3H3N2 is excessive, the excess imidazole ionic liquid (R 41 O)(R 42 O)(R 43 O)SiR1C3H3N2 can promote the reaction of the two in the direction of superpositive reaction and improve the reaction efficiency. It should be noted that imidazole ionic liquid (R 41 O)(R 42 O)(R 43 When the content of O)SiR1C3H3N2 is too high, it is easy to cause residues in the prepared imidazolium salt ionic liquid, affecting the purity and performance of the imidazolium salt ionic liquid.
[0092] The mixed raw materials are heated to obtain imidazole ionic liquid (R 41 O)(R 42 O)(R 43 O) SiR1C3H3N2 reacts with organic matter A-R2-R3 to generate an imidazole type ionic liquid whose anion is a halogen anion. The reaction formulas of the two are as follows:
[0093]
[0094] In a possible implementation, the heating reaction temperature is 50-80°C and the reaction time is 24-72 hours. Under such conditions, the imidazole ionic liquid (R41 O)(R 42 O)(R 43 O)SiR1C3H3N2 reacts with organic matter A-R2-R3 to generate a target ionic liquid, and the occurrence of side reactions can be reduced, thereby improving the yield and purity of the obtained ionic liquid.
[0095] When the target imidazolium salt ionic liquid is an imidazolium salt ionic liquid whose anion is a halogen anion, the target product can be obtained after the reaction is completed.
[0096] In some possible embodiments, the anion in the target imidazolium salt ionic liquid is not a halogen anion. 41 O)(R 42 O)(R 43 O) SiR1C3H3N2 is mixed with the organic matter A-R2-R3, and after the heating reaction is completed, the target anion salt (the anion in the anion salt is the anion in the target imidazole-type ionic liquid) is added to the reaction system to replace the halogen in the synthesized ionic liquid to obtain the imidazole salt ionic liquid provided in the first aspect of the embodiment of the present application, in which the anion is not a halogen anion. Exemplarily, the target anion salt can be bis(pentafluoroethylsulfonyl)imide salt.
[0097] The preparation method of the imidazolium salt ionic liquid provided in the embodiment of the present application only requires the imidazolium type ionic liquid (R 41 O)(R 42 O)(R 43 O) SiR1C3H3N2 and organic matter A-R2-R3 are heated to react to obtain the imidazole salt ionic liquid of the first aspect of the present application. The method is simple to operate, the process is easy to control, and the production cost of the imidazole salt ionic liquid can be controlled.
[0098] The third aspect of the embodiment of the present application provides a surface-modified silica, including silica particles, and a modifier bound to the surface of the silica particles, wherein the modifier includes the product obtained by removing the alkyl group in the alkoxysilyl group from the imidazolium salt ionic liquid as described in the first aspect of the embodiment of the present application.
[0099] The surface-modified silica provided in the embodiment of the present application is shown in the following structure 3, wherein: Represents a hydroxyl site on the silica surface
[0100]
[0101] The surface-modified silica provided by the present application has the product of removing the alkyl group in the alkoxysilyl group from the imidazolium salt ionic liquid of the first aspect of the present application combined on the surface of the silica particles. The silica particles introduced with the imidazolium salt ionic liquid have enriched the types of functional groups at the single silanol site and increased the grafting density. These functional groups promote the contact between silica and the organic resin, thereby improving the compatibility between the two.
[0102] In the embodiment of the present application, the imidazolium salt ionic liquid is an imidazolium salt ionic liquid shown in Formula 1,
[0103]
[0104] Among them, X - , R1, R2, R 41 , R 42 , R 43 The selection and possible implementation of imidazolium salt ionic liquids are as described above, and will not be repeated here to save space.
[0105] In a possible implementation, the weight of the modifier is 0.2-5% of the weight of the silica particles. In this case, the modifier is grafted onto the surface of the silica particles at a suitable density to improve the surface properties of the silica, thereby improving the compatibility between the silica and the organic resin.
[0106] In a possible implementation, the particle size of the silica particles is 300 nm to 5 μm. In this case, the silica particles have a suitable specific surface area and number of surface hydroxyl groups, which are conducive to the grafting of macromolecular imidazole salt ionic liquid modifiers.
[0107] In a possible implementation, the modified compound is a product obtained by removing the alkyl group in the alkoxysilyl group from an imidazolium salt ionic liquid. In this case, there is only one type of modification on the surface of the silica particles, which is the product of the hydrolysis of the imidazolium salt ionic liquid shown in Formula 1. The imidazolium salt ionic liquid increases the type of the hanging energy group and the grafting density of the silica, thereby improving the compatibility with the organic resin.
[0108] The surface-modified silica provided in the third aspect of the embodiments of the present application can be prepared by the following method.
[0109] In a fourth aspect, the present invention provides a method for preparing surface-modified silicon dioxide, comprising the following steps:
[0110] The silicon dioxide powder is mixed with the imidazolium salt ionic liquid of the first aspect of the present application, and reacted at a temperature of 80 to 200° C. to obtain the surface-modified silicon dioxide of the second aspect of the present application.
[0111] The method for preparing surface-modified silica provided in the embodiment of the present application comprises reacting silica powder and an imidazolium salt ionic liquid shown in Formula 1 at a suitable temperature to obtain silica surface-modified with an imidazolium salt ionic liquid. The method is simple and easy to control. More importantly, the silica surface-modified with an imidazolium salt ionic liquid obtained in the method has increased types and quantities of unsaturated functional groups on its surface, which can improve its compatibility with organic resins.
[0112] In a possible implementation, the weight of the imidazolium salt ionic liquid is 0.2-5% of the weight of the silicon dioxide powder, and the two are mixed. In this case, the surface-modified silicon dioxide obtained has the imidazolium salt ionic liquid grafted on the surface of the silicon dioxide particles at a suitable density, thereby improving the surface properties of the silicon dioxide and further improving the compatibility between the silicon dioxide and the organic resin.
[0113] In a possible implementation, imidazolium salt ionic liquid is added to silicon dioxide powder, and the silicon dioxide powder is mixed with the imidazolium salt ionic liquid of the first aspect of the present application.
[0114] The mixed silicon dioxide powder is reacted with the imidazolium salt ionic liquid of the first aspect of the present application at a suitable heating temperature, and the alkoxysilyl groups in the imidazolium salt ionic liquid are hydrolyzed and grafted onto the surface of the silicon dioxide particles.
[0115] The reaction equation is shown below.
[0116]
[0117] In the embodiment of the present application, the silicon dioxide powder reacts with the imidazolium salt ionic liquid at a temperature of 80 to 200° C. If the reaction temperature is too low, the hydrolysis of the alkoxysilyl group in the imidazolium salt ionic liquid is affected, which is not conducive to the grafting of the imidazolium salt ionic liquid on the surface of the silicon dioxide particles; if the reaction temperature is too high, more side reactions will be introduced, affecting the preparation effect.
[0118] In a possible implementation, the reaction time is 0.5-3 hours. At a reaction temperature of 80-200° C., the silicon dioxide powder and the imidazolium salt ionic liquid of the first aspect of the present application react for 0.5-3 hours, which is conducive to a full reaction between the two.
[0119] In a possible implementation, after the reaction is completed, the reaction product is collected. In some embodiments, the reaction system is vacuum filtered, washed multiple times with pure water and ethanol, respectively, and then dried at 50 to 130°C. Wherein, pure water is used to remove unreacted inorganic ions, and ethanol is used to remove ionic liquids. Exemplarily, the filtrate is washed three or four times with pure water and ethanol, respectively, and the reaction product is collected. In some embodiments, the reaction system is subjected to reduced pressure distillation, and the reaction product is collected. In some embodiments, the reaction system is dried under vacuum conditions, and the reaction product is collected. In some embodiments, the reaction product is dried and collected by freeze drying.
[0120] In a fifth aspect, an embodiment of the present application provides a composite material, comprising an organic resin and a filler, and the filler is the surface-modified silica of the third aspect of the embodiment of the present application.
[0121] The composite material provided in the embodiment of the present application includes an organic resin and a surface-modified silica filler. Since the surface of the silica is modified with an imidazolium salt ionic liquid, the compatibility between the organic resin and the silica filler can be enhanced, and the filling rate and dispersibility of the silica in the organic resin can be improved, so that the silica can fully play the role of reducing the thermal expansion performance of the composite material.
[0122] In a possible implementation, the weight ratio of the organic resin to the filler is 7:3 to 4:6, based on 10 parts by weight of the composite material. When the contents of the organic resin and the filler are within this range, the compatibility between the organic resin and the silica filler is enhanced, which is beneficial to improving the filling rate and dispersibility of silica in the organic resin, thereby giving the composite material better reliability.
[0123] In a possible implementation, the organic resin is selected from at least one of bisphenol F epoxy resin and bisphenol A epoxy resin. Such organic resin is compounded with surface-modified silica filler, and the two increase their compatibility with each other through the imidazolate ionic liquid (the product of the hydrolysis of the imidazolate ionic liquid shown in Formula 1) on the surface of silica, thereby improving the uniformity and performance stability of the composite material, and helping silica to fully play the role of reducing the thermal expansion performance of the composite material.
[0124] In a sixth aspect, an embodiment of the present application provides an electronic component, including a printed circuit board, a filling glue layer located on at least one surface of the printed circuit board, and a chip arranged on the side of the filling glue layer away from the printed circuit board, wherein the filling glue in the filling glue layer is the composite material provided in the fifth aspect of the embodiment of the present application.
[0125] The electronic components provided in the embodiments of the present application, the filling glue includes an organic resin and a surface-modified silica filler. Since the surface of the silica is modified with an imidazolium salt ionic liquid, a plurality of identical or different functional groups are simultaneously grafted on a single silanol site of the silica, thereby achieving the effect of doubling the compatibility of the silica filler and the organic resin, thereby improving the effective filling rate and dispersion uniformity of the silica in the organic resin, enhancing the fluidity of the filling glue, reducing the thermal expansion coefficient, and ultimately improving the reliability of the chip.
[0126] For example, Figure 1 As shown, the electronic component includes a printed circuit board 1, a solder ball 4 arranged on at least one surface of the printed circuit board 1, a chip 2 fixed on the printed circuit board by the solder ball 4, and a filling glue layer 3 filled between the printed circuit board 1 and the chip 2, and the filling layer 3 is used to protect and fix the solder ball 4. Among them, the filling glue in the filling glue layer 3 is a composite material of an organic resin and a silica filler, and the silica filler is a surface-modified silica filler provided in an embodiment of the present application.
[0127] In some embodiments, the electronic component further includes a packaging component 5, and the packaging component 5 seals the chip 2 on the surface of the printed circuit board 1. Exemplarily, the packaging material of the packaging component 5 is epoxy mold resin.
[0128] In a possible implementation, the weight ratio of the organic resin to the filler is 50-40:50-60, based on 10 parts by weight of the composite material. When the contents of the two are within this range, the silicon dioxide is evenly dispersed in the composite material formed by the silicon dioxide and the organic resin, thereby giving the filler better thermal stability and improving the reliability of electronic components.
[0129] In a possible implementation, the organic resin in the filling glue is selected from at least one of bisphenol F epoxy resin and bisphenol A epoxy resin. These organic resins and surface-modified silica fillers are used as the filling glue layer between the printed circuit board and the chip in the electronic components. Since the surface-modified silica has good compatibility with the organic resin, the silica filler can be effectively filled and evenly dispersed in the organic resin, thereby enhancing the fluidity of the filling glue, reducing the thermal expansion coefficient, and ultimately effectively improving the reliability of the chip.
[0130] A seventh aspect of the embodiments of the present application provides a chip protection shell, which is made of the composite material provided in the fifth aspect of the embodiments of the present application.
[0131] The chip protection shell provided in the embodiment of the present application comprises raw materials including an organic resin and a surface-modified silica filler. Since the surface of the silica is modified with an imidazolium salt ionic liquid, a plurality of identical or different functional groups are simultaneously grafted onto a single silanol site of the silica, thereby achieving an effect of doubling the compatibility of the silica filler and the organic resin, thereby improving the effective filling rate and dispersion uniformity of the silica in the organic resin, enhancing the fluidity of the chip protection shell material, reducing the thermal expansion coefficient, and ultimately achieving excellent reliability.
[0132] The composite material used as a chip protection shell provided in the embodiment of the present application is also called epoxy mold resin.
[0133] refer to Figure 1 The electronic components provided include a printed circuit board 1, a solder ball 4 disposed on at least one surface of the printed circuit board 1, a chip 2 fixed on the printed circuit board by the solder ball 4, a filling glue layer 3 filled between the printed circuit board 1 and the chip 2, and a packaging component 5, the packaging component 5 seals the chip 2 on the surface of the printed circuit board 1. Exemplarily, the packaging material of the packaging component 5 is an epoxy mold resin. In some embodiments, the epoxy mold resin includes a composite material formed by an organic resin and a silica filler, and the silica filler is a surface-modified silica filler provided in an embodiment of the present application.
[0134] In a possible implementation, the weight ratio of the organic resin to the filler is 2:8 to 1:9 based on 10 parts by weight of the composite material. When the contents of the two are within this range, the silicon dioxide is evenly dispersed in the composite material formed by the silicon dioxide and the organic resin, thereby giving the chip protection shell material, i.e., the epoxy mold resin, better thermal stability, and improving the reliability of the chip protection shell.
[0135] In a possible implementation, the organic resin in the epoxy mold resin is selected from at least one of bisphenol F epoxy resin, bisphenol A epoxy resin, dicyclopentadiene epoxy resin, biphenyl epoxy resin, and o-cresol linear epoxy resin. These organic resins are mixed with surface-modified silica fillers and used as chip protection shell materials. Since the surface-modified silica has good compatibility with the organic resin, the silica filler can be effectively filled and evenly dispersed in the organic resin, thereby enhancing the fluidity of the chip protection shell material, i.e., the epoxy mold resin, and reducing the thermal expansion coefficient, and finally obtaining excellent reliability.
[0136] An eighth aspect of the embodiments of the present application provides a conductor, comprising a conductor core, and a stacked insulating adhesive coated on the surface of the conductor core or formed on the surface of the conductor core joint, wherein the stacked insulating adhesive is made of the composite material provided in the fifth aspect of the embodiments of the present application.
[0137] The wire provided in the embodiment of the present application comprises an organic resin and a surface-modified silica filler. Since the surface of the silica is modified with an imidazolium salt ionic liquid, a plurality of identical or different functional groups are simultaneously grafted onto a single silanol site of the silica, thereby achieving an effect of doubling the compatibility of the silica filler and the organic resin, thereby improving the effective filling rate and dispersion uniformity of the silica in the organic resin, enhancing the fluidity of the stacked insulating adhesive, reducing the thermal expansion coefficient, and ultimately obtaining excellent thermal insulation and insulating properties.
[0138] In a possible implementation, the weight ratio of the organic resin to the filler is 6:4 to 4.5:5.5, based on 10 parts by weight of the total composite material. When the contents of the two are within this range, the silicon dioxide is evenly dispersed in the composite material formed by the silicon dioxide and the organic resin, thereby reducing the thermal expansion coefficient of the stacked insulating adhesive, and ultimately obtaining excellent thermal insulation and insulating properties.
[0139] In a possible implementation, the organic resin is selected from at least one of bisphenol A epoxy resin, naphthalene epoxy resin, and dicyclopentadiene epoxy resin. These organic resins are mixed with surface-modified silica fillers and used as chip protection shell materials. Since the surface-modified silica has good compatibility with the organic resin, the silica filler can be effectively filled and evenly dispersed in the organic resin, thereby enhancing the fluidity of the stacked insulating glue, reducing the thermal expansion coefficient, and ultimately obtaining excellent thermal insulation and insulation properties.
[0140] The following describes the invention in conjunction with specific embodiments.
[0141] Example 1
[0142] A surface-modified silicon dioxide, the preparation method of which is as follows:
[0143] Under nitrogen protection, N-imidazolepropyltrimethoxysilane and 1-bromo-5-carbonyl-7-octene were mixed in a molar ratio of 1.2:1, and reacted at a temperature of 80°C for 48 hours. The reaction process was maintained in a nitrogen atmosphere. After the reaction was completed, the mixture was washed and dried. The obtained product was mixed with a bis(pentafluoroethylsulfonyl)imide salt solution to make the Br in the product - After the replacement reaction is completed, the product is collected, washed, purified and dried to obtain the desired imidazole ionic liquid. The chemical reaction formula of this step is as follows:
[0144]
[0145]
[0146] 0.4 parts of the above-mentioned imidazole ionic liquid were added to 20 parts by weight of silicon dioxide powder with an average particle size of 1 micron, and the mixture was reacted at 120°C for 2 hours. The product obtained by the reaction was vacuum filtered, washed with pure water and ethanol three times respectively, and vacuum dried at 50°C to obtain the final modified silicon oxide powder.
[0147] Example 2
[0148] A surface-modified silicon dioxide, the preparation method of which is as follows:
[0149] Under nitrogen protection, N-imidazolepropyltrimethoxysilane and 1-bromo-7-carbonyl-3,8-nonadiene were mixed in a molar ratio of 1.4:1, and reacted at a temperature of 60°C for 48 hours. The reaction process was maintained in a nitrogen atmosphere. After the reaction was completed, the mixture was washed and dried; the obtained product was mixed with a bis(pentafluoroethylsulfonyl)imide salt solution to make the Br in the product - After the replacement reaction is completed, the product is collected, washed, purified and dried to obtain the desired imidazole ionic liquid. The chemical reaction formula of this step is as follows:
[0150]
[0151] 0.8 parts of the above-mentioned imidazole ionic liquid were added to 20 parts by weight of silicon dioxide powder with an average particle size of 1 micron, and the mixture was reacted at 140°C for 1 hour. The product obtained by the reaction was vacuum filtered, washed with pure water and ethanol three times respectively, and vacuum dried at 50°C to obtain the final modified silicon oxide powder.
[0152] Example 3
[0153] A surface-modified silicon dioxide, the preparation method of which is as follows:
[0154] Under nitrogen protection, N-imidazolepropyltrimethoxysilane and 2-carbonyl-3-bromomethyl-3,5-heptadiene were mixed in a molar ratio of 1.3:1, and reacted at a temperature of 65°C for 48 hours. The reaction process was maintained in a nitrogen atmosphere. After the reaction was completed, the product was washed and dried; the obtained product was mixed with a bis(pentafluoroethylsulfonyl)imide salt solution to make the Br in the product - After the replacement reaction is completed, the product is collected, washed, purified and dried to obtain the desired imidazole ionic liquid. The chemical reaction formula of this step is as follows:
[0155]
[0156] 0.7 parts of the above-mentioned imidazole ionic liquid were added to 20 parts by weight of silicon dioxide powder with an average particle size of 1 micron, and the mixture was reacted at a temperature of 150° C. for 1.5 hours. The product obtained by the reaction was vacuum filtered, washed with pure water and ethanol three times respectively, and vacuum dried at 50° C. to obtain the final modified silicon oxide powder.
[0157] Example 4
[0158] A surface-modified silicon dioxide, the preparation method of which is as follows:
[0159] Under nitrogen protection, N-imidazolepropyltrimethoxysilane and 1-bromo-5-carbonyl-7-octene were mixed in a molar ratio of 1.2:1, and reacted at 80°C for 48 hours. The reaction was maintained under nitrogen atmosphere. After the reaction, the mixture was washed and dried. The obtained product was mixed with lithium hexafluorophosphate solution to make Br in the product - Replace with F - After the replacement reaction is completed, the product is collected, washed, purified and dried to obtain the desired imidazole ionic liquid. The chemical reaction formula of this step is as follows:
[0160]
[0161] 0.4 parts of the above-mentioned imidazole ionic liquid were added to 20 parts by weight of silicon dioxide powder with an average particle size of 1 micron, and the mixture was reacted at 120°C for 2 hours. The product obtained by the reaction was vacuum filtered, washed with pure water and ethanol three times respectively, and vacuum dried at 50°C to obtain the final modified silicon oxide powder.
[0162] Example 5
[0163] A surface-modified silicon dioxide, the preparation method of which is as follows:
[0164] Under nitrogen protection, N-imidazolepropyltrimethoxysilane and 1-bromo-2-vinyl acetate were mixed in a molar ratio of 1.3:1, and reacted at a temperature of 80°C for 48 hours. The reaction process was maintained in a nitrogen atmosphere. After the reaction was completed, the mixture was washed and dried. The obtained product was mixed with a bis(pentafluoroethylsulfonyl)imide salt solution to make the Br in the product - After the replacement reaction is completed, the product is collected, washed, purified and dried to obtain the desired imidazole ionic liquid. The chemical reaction formula of this step is as follows:
[0165]
[0166] 0.8 parts of the above-mentioned imidazole ionic liquid were added to 20 parts by weight of silicon dioxide powder with an average particle size of 1 micron, and the mixture was reacted at 140°C for 1 hour. The product obtained by the reaction was vacuum filtered, washed with pure water and ethanol three times respectively, and vacuum dried at 50°C to obtain the final modified silicon oxide powder.
[0167] Example 6
[0168] A surface-modified silicon dioxide, the preparation method of which is as follows:
[0169] Under nitrogen protection, N-imidazole butyltrimethoxysilane and 1-(4-(2-bromoethyl)phenyl)but-3-en-1-one were mixed in a molar ratio of 1.3:1, and reacted at a temperature of 80°C for 48 hours, with a nitrogen atmosphere maintained during the reaction. After the reaction, the product was washed and dried; the obtained product was mixed with a bis(pentafluoroethylsulfonyl)imide salt solution to make the Br in the product - After the replacement reaction is completed, the product is collected, washed, purified and dried to obtain an imidazole-type ionic liquid as shown below. The chemical reaction formula of this step is as follows:
[0170]
[0171] 0.8 parts of the above-mentioned imidazole ionic liquid were added to 20 parts by weight of silicon dioxide powder with an average particle size of 1 micron, and the mixture was reacted at 140°C for 1 hour. The product obtained by the reaction was vacuum filtered, washed with pure water and ethanol three times respectively, and vacuum dried at 50°C to obtain the final modified silicon oxide powder.
[0172] Comparative Example 1
[0173] A surface-modified silicon dioxide, the preparation method of which is as follows:
[0174] 0.4 parts by weight of 3-aminopropyltrimethoxysilane coupling agent was added to 20 parts by weight of silicon oxide powder with an average particle size of 2 microns, and the mixture was reacted at 120°C for 2 hours. The product obtained by the reaction was vacuum filtered, washed with pure water and ethanol three times respectively, and vacuum dried at 50°C to obtain the final modified silicon oxide powder.
[0175] Comparative Example 2
[0176] 0.2 parts by weight of N-cyclohexyl-γ-aminopropyltrimethoxysilane coupling agent was added to 20 parts by weight of silicon oxide powder with an average particle size of 1 micron, and the mixture was reacted at 120° C. for 2 hours. The product obtained by the reaction was vacuum filtered, washed with pure water and ethanol three times respectively, and vacuum dried at 50° C. to obtain the final modified silicon oxide powder.
[0177] The surface modified silica prepared in Examples 1 to 6 and Comparative Examples 1 to 2 was added to bisphenol F epoxy resin at a weight percentage of 55%, and the composite material was fully degassed and mixed to obtain the composite material, and the viscosity, surface energy, and CTE of the composite material before and after curing were measured. The viscosity was measured by a rheometer, the CTE was measured by a TMA instrument, and the surface energy was measured by an inverse gas chromatography.
[0178] The measurement results are summarized in Table 1, wherein CTE1 represents the thermal expansion coefficient of the composite material before curing, and CTE2 represents the thermal expansion coefficient of the composite material after curing.
[0179] Table 1
[0180]
[0181] As can be seen from Table 1, compared with silica modified with a silane coupling agent, the composite material formed by the imidazole-type ionic liquid-modified silica provided in the embodiment of the present application and the bisphenol F epoxy resin has a lower system viscosity, better fluidity, and reduced surface energy; the thermal expansion coefficient of the composite material before and after curing is lower than that of the comparative example, which shows that the thermal expansion performance of the composite material provided in the embodiment of the present application is relatively stable.
[0182] The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. An imidazolium salt ionic liquid, characterized in that: Its general structural formula is shown in Formula 1 below: In formula 1, X - is selected from one of bis(pentafluoroethylsulfonyl)imino anions and halogen anions, and R1 and R2 are each independently selected from -CH2-, -C2H4-, -C3H6-, -C4H8-, -C5H 10 -or-C6H 12 -, R3 is a group containing two or more unsaturated functional groups selected from -COCH2CH=CH2, -CH=CHCH2CH2COCH=CH2, -C(COCH3)=CHCH=CHCH3, -CH=CHCH2CH2COOCH=CH2 or -C6H5-COCH2CH=CH2, R 41 , R 42 , R 43 Each is independently selected from an alkyl group having 1 to 4 carbon atoms.
2. The imidazolium salt ionic liquid according to claim 1, characterized in that The R 41 , the R 42 , the R 43 Each is independently selected from methyl or ethyl.
3. The imidazolium salt ionic liquid according to any one of claims 1 to 2, characterized in that The imidazolium salt ionic liquid comprises the following structure: 。 4. A method for preparing an imidazolium salt ionic liquid, characterized in that: The steps include: Provide an imidazolium-type ionic liquid (R 41 O)(R 42 O)(R 43 O) SiR1C3H3N2 and an organic compound A-R2-R3, wherein A is a halogen, and R1 and R2 are each independently selected from -CH2-, -C2H4-, -C3H6-, -C4H8-, -C5H 10 -or-C6H 12 -, R3 is a group containing two or more unsaturated functional groups selected from -COCH2CH=CH2, -CH=CHCH2CH2COCH=CH2, -C(COCH3)=CHCH=CHCH3, -CH=CHCH2CH2COOCH=CH2 or -C6H5-COCH2CH=CH2, R 41 , R 42 , R 43 Each is independently selected from an alkyl group having 1 to 4 carbon atoms; In an inert atmosphere or under vacuum conditions, the imidazolium ionic liquid (R 41 O)(R 42 O)(R 43 O) SiR1C3H3N2 is mixed with an organic substance A-R2-R3, and heated to react to obtain the imidazolium salt ionic liquid according to any one of claims 1 to 3; or the imidazolium ionic liquid (R 41 O)(R 42 O)(R 43 O) SiR1C3H3N2 is mixed with the organic matter A-R2-R3, heated for reaction, and after the reaction is completed, an anion salt is added to the reaction system to replace the halogen in the synthesized ionic liquid to obtain the imidazole salt ionic liquid according to any one of claims 1 to 3 。 5. The method for preparing an imidazole salt ionic liquid according to claim 4, wherein: The imidazolium ionic liquid (R 41 O)(R 42 O)(R 43 In the step of mixing SiR1C3H3N2 with the organic matter A-R2-R3, the imidazole type ionic liquid (R 41 O)(R 42 O)(R 43 O) The molar ratio of SiR1C3H3N2 to the organic matter A-R2-R3 is 1~1.5:
1.
6. The method for preparing an imidazolium salt ionic liquid according to claim 5, wherein: The temperature of the heating reaction is 50-80° C., and the reaction time is 24-72 hours.
7. A surface-modified silica, characterized in that: The invention comprises silicon dioxide particles and a modification combined on the surface of the silicon dioxide particles, wherein the modification comprises a product obtained by removing the alkyl group in the alkoxysilyl group from the imidazolium salt ionic liquid as described in any one of claims 1 to 3.
8. The surface-modified silica according to claim 7, characterized in that The weight of the modifier is 0.2-5% of the weight of the silica particles.
9. The surface-modified silica according to claim 7, characterized in that The particle size of the silicon dioxide particles is 300 nm to 5 μm.
10. The surface-modified silicon dioxide according to any one of claims 7 to 9, characterized in that The modified product is a product obtained by removing the alkyl group in the alkoxysilyl group from the imidazolium salt ionic liquid.
11. A method for preparing surface-modified silicon dioxide, characterized in that: The steps include: The silicon dioxide powder is mixed with the imidazolium salt ionic liquid as described in any one of claims 1 to 3, and reacted at a temperature of 80 to 200° C. to obtain the surface-modified silicon dioxide as described in any one of claims 7 to 10.
12. The method for preparing surface-modified silicon dioxide according to claim 11, characterized in that: The reaction time is 0.5-3 hours.
13. A composite material, characterized in that: It comprises an organic resin and a filler, and the filler is the surface-modified silica according to any one of claims 7 to 10.
14. The composite material according to claim 13, characterized in that Based on 10 parts by weight of the composite material, the weight ratio of the organic resin to the filler is 7:3-4:
6.
15. The composite material according to claim 13, characterized in that The organic resin is selected from at least one of bisphenol F epoxy resin and bisphenol A epoxy resin.
16. An electronic component, comprising a printed circuit board, a filling adhesive layer located on at least one surface of the printed circuit board, and a chip arranged on a side of the filling adhesive layer away from the printed circuit board, characterized in that: The filling glue in the filling glue layer is the composite material according to claim 13.
17. The electronic component according to claim 16, characterized in that: Based on 10 parts by weight of the composite material, the weight ratio of the organic resin to the filler is 5:5 to 4:
6.
18. The electronic component according to claim 16 or 17, characterized in that: The organic resin is selected from at least one of bisphenol F epoxy resin and bisphenol A epoxy resin.
19. A chip protection shell, characterized in that: The chip protection shell is made of the composite material according to claim 13.
20. The chip protection housing according to claim 19, characterized in that: Based on 10 parts by weight of the composite material, the weight ratio of the organic resin to the filler is 2:8 to 1:
9.
21. The chip protection housing according to claim 19 or 20, characterized in that: The organic resin is selected from at least one of bisphenol F epoxy resin, bisphenol A epoxy resin, dicyclopentadiene epoxy resin, biphenyl epoxy resin and o-cresol linear epoxy resin.
22. A conductor, comprising a conductor core, and a stacked insulating adhesive coated on the surface of the conductor core or formed on the surface of the conductor core joint, characterized in that: The stacked insulating adhesive is made of the composite material according to claim 13.
23. The guide wire according to claim 22, characterized in that Based on 10 parts by weight of the composite material, the weight ratio of the organic resin to the filler is 6:4 to 4.5:5.
5.
24. The guide wire according to claim 22 or 23, characterized in that: The organic resin is selected from at least one of bisphenol A epoxy resin, naphthalene epoxy resin and dicyclopentadiene epoxy resin.
Citation Information
Patent Citations
Catalyst for synthesizing vinyl chloride monomer and preparation method thereof
CN102671701A
Composite semipermeable membrane
CN102834167A
Dodecyl-benzylimidazole bonded silica gel solid-phase extractant, preparation method and application thereof
CN104587989A
Bismuth silicon oxyhalide material as well as preparation method and application thereof
CN111604067A
Novel bi-functional ionic liquids and the preparation method thereof
KR1020080054058A